2022
DOI: 10.1007/s00203-022-02799-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biodegradable film mulching on bacterial diversity in soils

Abstract: The spread of biodegradable plastic lm (BDFs) not only increase grain yield but also reduce the environmental pollution from plastic lm to a large extent. Soil microbes have been considered to be involved in biodegradation processes.However, the study of microbes diversity in soil mulched with biodegradable plastic lm remains limited. Here, we compared the diversity of microbes between soils with biodegradable lm and non-biodegradable lm (NBDF) mulch.The results showed that BDFs affected on the soil quality pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 63 publications
0
2
1
Order By: Relevance
“…This is different from the results obtained in this study [39]. First, this may be due to the different mulching materials; the sensitivity of soil microorganisms to changes in the external environment is different [40]. Second, this may be because this study is a short-term experiment and has little effect on soil fungal diversity [41].…”
Section: Effects Of Different Film Mulching Methods On Soil Microbial...contrasting
confidence: 80%
“…This is different from the results obtained in this study [39]. First, this may be due to the different mulching materials; the sensitivity of soil microorganisms to changes in the external environment is different [40]. Second, this may be because this study is a short-term experiment and has little effect on soil fungal diversity [41].…”
Section: Effects Of Different Film Mulching Methods On Soil Microbial...contrasting
confidence: 80%
“…In the present study, the findings revealed that different biodegradable films had different degrees of field degradation, which may be caused by different formulations of biodegradable films leading to different effects of soil microorganisms on them (Eksiler et al 2017 ; Xue et al 2021 ). Additionally, the degradation of three biodegradable films began to be induced at 43 ~ 59d after mulching, and large cracks appeared at 62 ~ 104d after mulching.…”
Section: Discussionmentioning
confidence: 77%
“…The gut microbiota plays a critical role in gut growth, nutrient absorption, and host health [21]. Higher Simpson index values indicate lower community diversity [22]. The MetR group had the richest microbiota species diversity compared to the CON group, as evidenced by the reduced Simpson indices.…”
Section: Discussionmentioning
confidence: 99%